The role of eicosanoids in experimental Lyme arthritis - Pratt, Carmela L.; Brown, Charles R. (Frontiers in Cellular and Infection Microbiology, 2014)
Experimental Lyme arthritis is an inflammatory arthritis caused by infection of mice with the spirochete, Borrelia burgdorferi. It recapitulates many of the disease parameters seen in human patients with Lyme arthritis, and thus serves as a model system for the investigation of disease pathogenesis. While much progress has been made in defining components of the immune response to Borrelia infection, an overall understanding of the host response leading to arthritis resistance or susceptibility remains elusive. In this review, we will focus on recent advancements of our understanding of the roles of eicosanoids as inflammatory mediators in the regulation of experimental Lyme arthritis. Eicosanoids, such as PGE2 and LTB4, are powerful regulators of inflammatory responses and thus may be important mediators of Lyme arthritis.